Nicotinamide Administration Improves Remyelination after Stroke - Congxiao Wang; Yi Zhang; Jie Ding; Zhen Zhao; Cheng Qian; Ying Luan; Gao-Jun Teng (Neural Plasticity)
Aims. Stroke is a leading cause of morbidity and mortality. This study aimed to determine whether nicotinamide administration could improve remyelination after stroke and reveal the underlying mechanism. Methods. Adult male C57BL/6J mice were intraperitoneally (i.p.) administered with nicotinamide (200 mg/kg, daily) or saline after stroke induced by photothrombotic occlusion of the middle cerebral artery. FK866 (3 mg/kg, daily, bis in die), an inhibitor of NAMPT, and ANA-12 (0.5 mg/kg, daily), an antagonist of tropomyosin-related kinase B (TrkB), were administered intraperitoneally 1 h before nicotinamide administration. Functional recovery, MRI, and histological assessment were performed after stroke at different time points. Results. The nicotinamide-treated mice showed significantly lower infarct area 7 d after stroke induction and significantly higher fractional anisotropy (FA) in the ipsilesional internal capsule (IC) 14 d after stroke induction than the other groups. Higher levels of NAD+, BDNF, and remyelination markers were observed in the nicotinamide-treated group. FK866 administration reduced NAD+ and BDNF levels in the nicotinamide-treated group. ANA-12 administration impaired the recovery from stroke with no effect on NAD+ and BDNF levels. Furthermore, lesser functional deficits were observed in the nicotinamide-treated group than in the control group. Conclusions. Nicotinamide administration improves remyelination after stroke via the NAD+/BDNF/TrkB pathway.